Lagged effect of daily surface acting on subsequent day's fatigue. Issue 15 (9th December 2016) - Zhang, Yucheng; Zhang, Long; Lei, Hui; Yue, Yumeng; Zhu, Jingtao
ABSTRACT: The present research investigated the causal relationship between daily surface acting and fatigue at the within-person level. With a longitudinal approach – experience sampling method – based on 10 successive days' data, this study explored the lagged consequence of service employees' daily surface acting. The results of multilevel analysis showed that the daily performance of surface acting decreased service employees' subsequent day's emotional well-being in the form of increased fatigue. Further, sleep conditions were found to alleviate this detrimental effect. This within-person level investigation of the causal lagged effect of daily surface acting and its moderating contextual factor complements the current emotional labor literature that has overly focused on the between-person level. The theoretical and managerial implications were discussed.